Association of distance to swine concentrated animal feeding operations with immune-mediated diseases: An exploratory gene-environment study. (January 2023) - Ayala-Ramirez, Montserrat; MacNell, Nathaniel; McNamee, Lucy E.; McGrath, John A.; Akhtari, Farida S.; Curry, Matthew D.; Dunnon, Askia K.; Fessler, Michael B.; Garantziotis, Stavros; Parks, Christine G.; Fargo, David C.; Schmitt, Charles P.; et al.
Graphical abstract: Highlights: Proximity to concentrated animal feeding operation is associated with autoimmunity. Proximity to CAFO is associated with rheumatoid arthritis. Xenobiotic response gene ARNT SNPs are associated with rheumatoid arthritis. AHR-ARNT pathway, vicinity to CAFO confer risk of some immune-mediated diseases. ARNT SNPs, CAFO vicinity are associated with autoimmune disease, rheumatoid arthritis. Abstract: Background: Concentrated animal feeding operations (CAFOs) are a source of environmental pollution and have been associated with a variety of health outcomes. Immune-mediated diseases (IMD) are characterized by dysregulation of the normal immune response and, while they may be affected by gene and environmental factors, their association with living in proximity to a CAFO is unknown. Objectives: We explored gene, environment, and gene-environment (GxE) relationships between IMD, CAFOs, and single nucleotide polymorphisms (SNPs) of prototypical xenobiotic response genes AHR, ARNT, and AHRR and prototypical immune response gene PTPN22 . Methods: The exposure analysis cohort consisted of 6, 464 participants who completed the Personalized Environment and Genes Study Health and Exposure Survey and a subset of 1, 541 participants who were genotyped. We assessed the association between participants' residential proximity to a CAFO in gene, environment, and GxE models. We recombined individual associations in a transethnic model using METAL meta-analysis. Results: In White participants, ARNT SNP rs11204735 was associated with autoimmune diseases and rheumatoid arthritis (RA), and ARNT SNP rs1889740 was associated with RA. In a transethnic genetic analysis, ARNT SNPs rs11204735 and rs1889740 and PTPN22 SNP rs2476601 were associated with autoimmune diseases and RA. In participants living closer than one mile to a CAFO, the log-distance to a CAFO was associated with autoimmune diseases and RA. In a GxE interaction model, White participants with ARNT SNPs rs11204735 and rs1889740 living closer than eight miles to a CAFO had increased odds of RA and autoimmune diseases, respectively. The transethnic model revealed similar GxE interactions. Conclusions: Our results suggest increased risk of autoimmune diseases and RA in those living in proximity to a CAFO and a potential role of the AHR-ARNT pathway in conferring risk. We also report the first association of ARNT SNPs rs11204735 and rs1889740 with RA. Our findings, if confirmed, could allow for novel genetically-targeted or other preventive approaches for certain IMD.